2016
DOI: 10.1002/phar.1874
|View full text |Cite
|
Sign up to set email alerts
|

White Paper on Natural Products

Abstract: The American College of Clinical Pharmacy (ACCP) published an initial white paper on herbal products in 2000. Since then, the global market for natural products has continued to expand, with tens of millions of consumers using such products on an annual basis in the United States alone. However, despite this expansion, natural products remain largely unregulated compared with prescription medications, have moderate- to low-level clinical evidence for efficacy, and continue to have safety concerns, including ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The prescription product is not approved for use specifically for SIB and may not be readily available in all pharmacies. The over‐the‐counter supplements are not regulated by the FDA; therefore, caution should be exercised when selecting these products, and insurance coverage may pose a challenge …”
Section: Review Of Available Data: Monotherapymentioning
confidence: 99%
“…The prescription product is not approved for use specifically for SIB and may not be readily available in all pharmacies. The over‐the‐counter supplements are not regulated by the FDA; therefore, caution should be exercised when selecting these products, and insurance coverage may pose a challenge …”
Section: Review Of Available Data: Monotherapymentioning
confidence: 99%
“…The pharmacist is the most commonly approached health professional for advice on natural products 1. However, an American College of Clinical Pharmacists White Paper in 2017 reported that pharmacists’ self-perceived preparedness for discussing natural products remained low, despite regular questions from patients 2. Simply discounting the value of natural products can negatively impact the patient-pharmacist relationship, especially when patient self-belief in natural products is strong 2.…”
Section: Introductionmentioning
confidence: 99%
“…However, an American College of Clinical Pharmacists White Paper in 2017 reported that pharmacists’ self-perceived preparedness for discussing natural products remained low, despite regular questions from patients 2. Simply discounting the value of natural products can negatively impact the patient-pharmacist relationship, especially when patient self-belief in natural products is strong 2. Systematic reviews of natural products may be a valuable source of information for practicing pharmacists because they efficiently describe the nature of the data available in a field and can reconcile conflicting information for readers 3,4…”
Section: Introductionmentioning
confidence: 99%
“…The year 2017 began with a themed issue on health care expenditures focusing on the rising costs of pharmaceuticals . An official statement was published on “Optimizing Specialty Drug Use”, a “Guideline on Clinical Pharmacist Competencies”, a “Template for Evaluating a Clinical Pharmacist”, and a “White Paper on Natural Products” …”
mentioning
confidence: 99%
“…4 An official statement was published on "Optimizing Specialty Drug Use", 5 a "Guideline on Clinical Pharmacist Competencies", 6 a "Template for Evaluating a Clinical Pharmacist", 7 and a "White Paper on Natural Products". 8 The continuing expansion and maturation of clinical pharmacy has created a need for information and knowledge exchange about Ó 2018 Pharmacotherapy Publications, Inc.…”
mentioning
confidence: 99%